UNDERGROUND ECONOMY: THE SHADOW EFFECT OF HUMAN TRAFFICKING - Amelia, Siti; Maria, Siti; Roy, Juliansyah; Darma, Dio Caisar; Pusriadi, Tommy (LIFE: International Journal of Health and Life-Sciences, 2019)
The purpose of the study is to analyze the causes and disadvantages of human trafficking, knowing the obstacles faced in the prevention and handling of human trafficking in Indonesia. The research is based on qualitative methods with a descriptive approach (semi-structure interview, observation and documentation) in 5 regions of Indonesia. The research findings state that these workers and Indonesia suffered losses, because they were carried out illegally and there was an underground economy. The causes of human trafficking are caused by economic, social, cultural and legal factors. Meanwhile, various obstacles faced by the Government of Indonesia, namely: funding, not all government agencies that deal with the problem, understand the procedures, and unclear restitution policies.